The Provision of Long-Term Credit and Firm Growth in Developing Countries - Watson, Jennifer (Asian Journal of Economics and Empirical Research, 2020)
This study evaluates the impact of the provision of long-term credit (LTC) on the growth of small and young firms in developing countries. The growth of firms is evaluated on the basis of employment growth and total sales. Credit provisions have also been collected from the short- and LTC extended to the private sector. This study uses data on firm levels from more than 19000 firms in 52 countries between 2006–2016. In order to avoid the endogeneity issues that usually occur in such studies, this study has implemented a cross-country model to evaluate the significance of total bank credit, both long- and short-term, on the growth of sales and employment. The econometric results indicate that the availability of short-term credit (STC) is more beneficial for the growth of the firms, i.e. STC was found to have a significant impact on employment growth and sales in small and young firms. Although positive, LTC seemed to have no significance in the growth of the small and young firms. This study suggests that the prime reason behind these results is the availability of long-term loans for small and young firms.